Development of a fully integrated hydrological fate and transport model for plant protection products: incorporating groundwater, tile drainage, and runoff - Callaghan, Michael V.; Frey, Steven K.; Miller, Killian; Hwang, Hyoun-Tae; Zolfaghari, Reza; Hammel, Klaus; Berg, Steven J.; Sudicky, Edward A. (Frontiers in Environmental Science, 2024)
IntroductionPlant protection products (PPPs) such as pesticides and herbicides are experiencing increased use worldwide. In the context of PPP authorization and registration, water exposure assessments (drinking water and aquatic exposure) use numerical modeling to simulate relevant hydrological processes and exposure pathways. A common practice for estimating PPP leaching to groundwater, PPP loading onto surface water via tile drainage, or PPP transport via runoff utilizes multiple one-dimensional models, each representing a separate exposure pathway. Separate analysis of individual exposure pathways can result in disparate assumptions being made that represent relative worst-case scenarios for each pathway, rather than an integrated reasonable worst-case scenario for all pathways.MethodsThe interplay between PPP degradation, leaching to groundwater, transport in tile drainage, and runoff is well-suited for simulation using an integrated surface–subsurface hydrologic and chemical fate and transport model. This study presents functionality added to HydroGeoSphere (HGS), a three-dimensional, fully integrated, surface–subsurface hydrologic model. HGS was verified against other recognized models: PRZM, HYDRUS, PEARL, PELMO, and MACRO. Added features include automatic irrigation, non-linear adsorption, temperature and soil water content-dependent degradation, and solute uptake by plant roots.Results and DiscussionHGS results for leaching of PPP mass to groundwater showed the highest correlation, lowest error, and lowest bias relative to PEARL model results. Simulation of macropore flow to tile drains in HGS produced an intermittent tile drain flow in summer that resulted in generally lower peak effluent concentrations compared to the MACRO model. Simulation of runoff in HGS produced a higher total runoff compared to the PRZM model, attributed to lower evapotranspiration in HGS. Use of the integrated HGS model resulted in a greater agreement in water balance components relative to using multiple models to simulate individual hydrologic pathways.